Pengaruh Perendaman Bahan Organik Air Kelapa dan Air Cucian Beras Terhadap Viabilitas dan Vigor Benih Timun Apel (Cucumis sp.) dalam Periode simpan yang berbeda - jujun hermawan; Kuswarini Sulandjari; Elia Azizah (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2021)
The purpose of this research is to get the obtain immersion of organic matter that gives the highest yields at the long of storage of the apple cucumber (Cucumis sp) seed. Research was conducted in the Laboratory of Agronomy of The Agricultural Faculty of the Singaperbangsa University. The method of research used experimental methods, using a Randomized Complete Design (RCD) with two factors. The first factor is the length of seed storage consisting of 0 weeks (T0), 4 weeks (T1), 8 weeks (T2), and 12 weeks (T3). The second factor are immersion with organic matter consisting of control (P1), coconut water (P2), and rice laundry water (P3). Each treatment was repeated thrice so that accrued 36 units of experiment. The results showed significant test don DMRT (Duncan Multiple Range Test) standard of 5%. The results showed that there is no effect of interaction between the long of seed storage with the immersion using organic matter on growing potential, germinating power, index vigor, greedy growing, speed growing. Independently long seed storage and immersion of organic matter provide significant result on the entire observed variable. Best yield obtained at length storage of 8 weeks by immersion using organic matter of rice water. Keyword: Cucumber apple, Organic matter, viability, vigor, storage.